Analisis Sektor Ekonomi Unggulan Kabupaten Bogor - Fitria, Aulia Octa; Erlianti, Zahrani; Desmawan, Deris (Universitas Labuhanbatu, 2022)
The development strategy is the key to the success of economic development, if implemented and based on the potential for reciprocity. Bogor Regency's economic growth from its leading sector. Therefore, it is important for Bogor Regency to understand the superior part which is equivalent to economic codification in current conditions. Although Bogor Regency does not yet know what its leading sectors are, it is not yet clear whether these superior sectors can assess current economic developments. This analysis was made with the aim of knowing the best sectors in the Bogor Regency area. This analysis uses the Shift Share & Location Quotient (LQ) Analysis Method.